Narrando a edição: escritores e editores na Trilogia obscena, de Hilda Hilst - Luciana Borges (Estudos de Literatura Brasileira Contemporânea)
This paper analyzes the construction of writers', editors' and readers' characters in the Trilogia obscena, by Hilda Hilst. From the character's creation and their unfolding, the Trilogia's narratives undertake a movement of the literature evaluation in terms of production, circulationand literary text's valuation. Thus, the obscenity, inscribed as the top layer of text, ends upbecoming the background for a discussion about the Brazilian's literary field.